Каузальные конструкции со словом абие в текстах житий (Causal Constructions with the Word абие in the Hagiographic Texts) - Lönngren, Tamara (Poljarnyj vestnik, 2000)
The aim of this article is to characterize and classify the causal constructions in which the word abie occurs in a collection of Hagiographic Texts from the fifteenth century (the author of the collection is the Russian monk Nil Sorsky), and to investigate the realization of one of the meanings of abie in a certain type of causal construction. The concluding part presents a semantic description of the word abie, which is frequently used in these constructions.